PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI - Ratnasari, Niki; Meita, Iren (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The research aims to analyze the influence of corporate characteristic on the disclosure of corporate social responsibility with institutional ownership as a moderating variable. The population of this research is manufacture companies listed in Indonesia Stock Exchange (IDK) 2011-2015. Research sampling used purposive sampling technique. There are 22 samples that meet the criteria as a sample of research with 5 years of observation. The total sample studied was 110. The multiple regression analysis was used for hypothesis testing. The results indicate that firm size, firm age, and leverage have a significant influence on the corporate social responsibility; and simultaneously firm size, firm age, and leverage have a significant influence on the corporate social responsibility. Meanwhile, institutional ownership weakens the effect of firm size on the disclosure of social responsibility. While institutional ownership weakens the effect of firm age and leverage on the disclosure of social responsibility. Keywords: Corporate Social Responsibility Disclosure, Firm Size, Firm Age, Leverage, Institutional ownership